Secagem de cenoura (Daucus carota L.) em microondas - Rosa, Juliana Gomes (Universidade Federal de São Carlos, 2010)
Carrot is a root plant of the same name, Daucus carota L.. This vegetable has a high consumption and its use as an ingredient in the formulation of industrial products has increased in recent years. The main appeal of the carrot is its high content of β-carotene. During harvest the carrots have 80 to 90% humidity and this high moisture content makes it a product with a short shelf life. Drying is an alternative to increase the shelf life of carrot. In addition, a drying operation is required to prepare the plant to participate in various formulations of industrial products. The study of carrot drying has been performed in several dryers and the quality of the product related to different processes. Drying in a microwave dryer has stood out in the drying of food, as its heating mode is different from conventional drying by hot air. Microwave drying can improve the quality of the final product. The purpose of this study is to analyze the drying of carrots in a microwave dryer, to evaluate the quality of the final product and to check whether the combination of vacuum drying will lead to an increase in the quality of the dried carrots. The monitoring of the kinetics of microwave drying and microwave vacuum drying was conducted and the relationship between the kinetics and process conditions, such as the carrot shape and the power used, was investigated. The influence of such processes in the characteristics of the final product was evaluated by determining the apparent density, real density, porosity, shrinkage, total β- carotene and rehydration. Also the desorption isotherms of carrots were determined at temperatures of 40°C and 50°C. The data of drying kinetics and desorption isotherms were fitted to models suggested in the literature in order to describe these processes. The results showed that the drying rate of carrot in a microwave dryer was affected by the carrot shape. The content of β-carotene was reduced with the increase of power applied. The microwave drying in vacuum produced carrots with higher porosity and lower shrinkage, but this characteristic was not reflected in the ability of rehydration, which was independent of the drying process. Of the models fitted to the experimental results, the Page model gave the best fit to the kinetics of drying and Peleg model gave the best fit to the kinetics of rehydration of carrots dried in a microwave dryer and a microwave drying in vacuum.
Keywords: Secagem; Cenoura; Microondas; ENGENHARIAS::ENGENHARIA QUIMICA